Structure Improvement and Control Algorithm Optimization-Based Ground Automatic Neutral-Section Passing Method for Train - Cheng, Shu; Liu, Chang; Yu, Tianjian; Xiang, Chaoqun; Tian, Pengfei; Li, Kaidi; Wu, Xun (IEEE journal of emerging and selected topics in power electronics, 2023)
Passing the neutral section (NS) can causes transient impact and speed loss of the train. Therefore, whether the potential danger of the pantograph-catenary system (OCS) can be eliminated under the condition of full-load operation becomes one of the essential factors for the safe and efficient operation of electric locomotives. This article proposes an advanced method to optimize the structure and control algorithm, according to the drawbacks of the existing methods, such as miniature circuit capacity, poor output driving ability, low control accuracy, and slow system response speed. In this method, the pantograph-catenary arc is restrained by controlling the dynamic alternating transfer of instantaneous power. Besides, the voltage premodulation algorithm is used to realize flexible voltage switching between different adjacent power supply arms. Compared with the existing methods, this method can provide better system response output capability, and this can effectively suppress transient impact and ensure full-load train operation safety. Finally, in terms of transient suppression effect and resistance to external environmental interference, a series of functional verification and horizontal comparison experiments have proved the feasibility, superiority, and robustness of this method.